2016
DOI: 10.5812/ircmj.27140
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Costs of Accidents Following the Establishment of the Health, Safety and Environment Management System (HSE-MS) for the Construction Industry in Tehran

Abstract: Background: Accidents in the construction industry are a significant problem in many countries around the world. Occupational accidents result in reduced working hours, loss of life, and other related costs. These accidents result in socio-economic losses such as disability support costs, loss of working time, and increased medical care needs. They also create a lot of waste for communities and labor organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Due to rapid changes of technology and occupational accidents that impose heavy costs (1,2), new approaches and improving safety management systems seems absolutely necessary, especially in oil industries, which have a high risk of accidents (3).…”
Section: Introductionmentioning
confidence: 99%
“…Due to rapid changes of technology and occupational accidents that impose heavy costs (1,2), new approaches and improving safety management systems seems absolutely necessary, especially in oil industries, which have a high risk of accidents (3).…”
Section: Introductionmentioning
confidence: 99%
“…Also communication at work identified as a significant risk factor for leg pain among dental jobs. In study by to monotonous work, high perceived work load, and time pressure, data also suggest that low control on the job and lack of social support by colleagues are positively associated with musculoskeletal disease (10)(11). In research among Iranian nurses and other research the results indicated that high prevalence of self-reported musculoskeletal symptoms at neck, wrist/hand reports, was associated with psychosocial factors and specifically stress (5-7), but in present study no association was found with stress.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Research findings indicated that perceived value to donors' satisfaction with path coefficient of 0.65 and service quality to perceived value with path coefficient of 0.43 have highest prediction power and impact, because perceived value is a powerful force in directing operations, attitudes, and judgments in all daily life aspects. [22][23][24][25][26] Since service quality affects perceived value and satisfaction of customers, thus accountability and responsibility of employees of blood transfusion organization, using efficient system and increasing employee capability is recommended. Furthermore, given impact of donors' expectations on perceived value, it can be stated that the model enjoys relatively suitable goodness of fit.…”
Section: Discussionmentioning
confidence: 99%